SWOT Analysis in the Development Strategy of Lettuce Farmer UMKM (Case Study of Umkm Alam Tani Hidrofarm Kudus) - Mafaticha, Anni; Andni, Riyan (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The development of the times brings a number of changes in life. UMKM or Micro, Small and Medium Enterprises have a central function to bring changes in improving the economy of a country. UMKM are also referred to as businesses that are able to survive in crisis conditions. UMKM are usually more elastic, flexible, and adaptive so that capital becomes the beginning in working on their business. Purpose. This study aims to determine the strengths, weaknesses, opportunities, and threats affecting the Kudus Hydrofarm Farming Nature. Method. The method used in this research is qualitative. The data used in this research is primary data by conducting interviews and observations at UMKM Alam Tani Hidrofarm Kudus. Results. The results of this study indicate that the strengths of Alam Tani Hidrofarm Kudus are reducing dependence on large agricultural land, good quality products, appropriate market segmentation. The weaknesses include the unstable availability of hydroponic lettuce to fulfil the demand for vegetables, the lack of variety of vegetable products, and the risk of technical failures in the hydroponic system that can disrupt production. Conclusion. The conclusion of this study is that Alam Tani Hydrofarm UMKM in Kudus has a SWOT analysis that identifies the strengths, weaknesses, opportunities, and threats faced by their business. From this analysis, UMKM have several alternative strategies that can be implemented to optimise their potential. By implementing appropriate strategies, UMKM are expected to overcome the challenges faced, capitalise on existing opportunities, and contribute to the growth of a sustainable agriculture sector as well as the overall economy.